Effect of Marketing Mix and E-Wom on Consumer Purchase Decisions by Moderating Buying Interest during the Covid'19 Pandemic - Ari Soeti Yani; Rana Rani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to determine the effect of marketing mix on consumer buying interest during the covid 19 pandemic. and word of mouth marketing through digital or Electronic Word of Mouth (E-WOM). This marketing is considered effective during a pandemic because of the trust, positive impression and experience by buyers of the services offered so that they are able to persuade, motivate potential buyers more in deciding to buy. Another strategy as a support is to include the provision of discounts. The number of samples taken as many as 100 people or more consumers. The method used is a survey method, the form of research used in verification and descriptive research. Data was collected through interviews and distributing questionnaires to respondents. The questionnaire was tested using a validity test, reliability test and classical assumption test. The results showed that the marketing mix had a significant effect on consumer buying interest. Partially, price and product have an effect on consumer buying interest, while promotion and place have no influence on consumer buying interest. The product variable has the strongest influence on consumer buying interest.